2020
DOI: 10.3390/microorganisms8050747
|View full text |Cite
|
Sign up to set email alerts
|

Antimicrobial Resistance Traits of Escherichia coli Isolated from Dairy Manure and Freshwater Ecosystems Are Similar to One Another but Differ from Associated Clinical Isolates

Abstract: Antimicrobial resistance (AMR) is a prevalent global health problem across human and veterinary medicine. The One Health approach to AMR is necessary to mitigate transmission between sources of resistance and decrease the spread of resistant bacteria among humans, animals, and the environment. Our primary goal was to identify associations in resistance traits between Escherichia coli isolated from clinical (n = 103), dairy manure (n = 65), and freshwater ecosystem (n = 64) environments within the same geograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…Providencia spp. are Gram negative, rod shaped, and facultative anaerobic bacteria which are part of the family Enterobacteriaceae (Beattie et al, 2020;Esperón et al, 2020;Massé et al, 2021). The well-studied species include P. stuartii, P. alcalifaciens, and, P. rettgeri with these bacteria linked to gastroenteritis, Urinary Tract Infections (UTIs) and bacteraemia (Holman et al, 2016;Chuppava et al, 2019;Esperón et al, 2020;Yoshizawa et al, 2020;Congilosi and Aga, 2021).…”
Section: Providencia Sppmentioning
confidence: 99%
See 2 more Smart Citations
“…Providencia spp. are Gram negative, rod shaped, and facultative anaerobic bacteria which are part of the family Enterobacteriaceae (Beattie et al, 2020;Esperón et al, 2020;Massé et al, 2021). The well-studied species include P. stuartii, P. alcalifaciens, and, P. rettgeri with these bacteria linked to gastroenteritis, Urinary Tract Infections (UTIs) and bacteraemia (Holman et al, 2016;Chuppava et al, 2019;Esperón et al, 2020;Yoshizawa et al, 2020;Congilosi and Aga, 2021).…”
Section: Providencia Sppmentioning
confidence: 99%
“…Information as to their infection of farm animals is limited, however, the genus has been cited as exhibiting high levels of antimicrobial resistance (AMR) (Esperón et al, 2020) and while infection by Providencia spp. is rare, there are potential reservoirs of ARGs in the wider environment (Beattie et al, 2020). It would be beneficial for future studies to investigate the prevalence the impact of Providencia spp.…”
Section: Providencia Sppmentioning
confidence: 99%
See 1 more Smart Citation
“…In areas that release treated wastewater into local receiving waters accessed by humans and animals, this evaluation is vital to reduce potential health risks. Previous studies by our labs have characterized antibiotic resistance phenotypes and genotypes of E. coli from manure, wastewater, sediment and surface waters, hospital wastewater, and clinical strains [ 10 , 18 , 19 ]. This study expands on our previous findings through the following aims: (i) to assess the presence of cefotaxime (CTX)-resistant Escherichia coli populations in hospital and urban WW; (ii) to compare resistance patterns among clinical ESBL-producing E. coli to urban and hospital WW strains within a defined geographical location; and (iii) to further assess the presence of virulence factors among cefotaxime resistant populations to provide a more complete public health risk analysis.…”
Section: Introductionmentioning
confidence: 99%
“…One of the published studies aimed to compare antimicrobial resistance (AMR) in extended-spectrum cephalosporin-resistant and generic E. coli from a One Health approach applied on a beef production system, identifying the municipal sewage as a hot spot for MDR emergence and dissemination [ 10 ]. Also published was a study that identified associations in resistance traits between E. coli isolated from clinical, dairy manure, and freshwater ecosystem environments concluding that manure and environmental isolates were significantly different from clinical isolates based on analyzed traits, suggesting more transmission occurs between these two sources in the sampled environment [ 11 ]. The same approach was held by a different study aiming at detecting several virulence factors genes (fimA, papC, papG III, cnf1, hlyA and aer) and to determine the conjugative capacity in a wide collection of ESBL-producing E. coli isolated from different sources (human, food, farms, rivers, and wastewater treatment plants), emphasizing the need of a specific surveillance program of AMR indicators in wastewaters from animal or human origin, in order to apply sanitary measures to reduce the burden of resistant bacteria arriving to risky environments such as WWTPs [ 12 ].…”
mentioning
confidence: 99%